Response on Growth and Production of Vetiver (Vetiveria zizanioides L.) on Gibberelin Under Salinity Stress Conditions - Aisar Novita; Nini Rahmawati; Fitra Syawal Harahap; Hilwa Walida; Abdul Rahman Cemda; Fitria; Hilda Julia; Rini Susanti; Bayu Pratomo; Silvia Nora; Merlyn Mariana; Arie Hapsani Hasan Basri (Indonesian Journal of Agricultural Research, 2021)
Vetiver (Vetiveria zizanioides L.) plants are able to protect the soil from erosion and are tolerant of salinity stress. However, at high salinity levels, vetiver plants show a decreasing growth. The application of gibberelin is expected to increase the growth of vetiver in salinity stress conditions. The purpose of this study was to evaluate the growth responsiveness and production of vetiver the application of gibberelin under salinity stress conditions. This research was conducted in the green house of the Faculty of Agiculture, Universitas Sumatera Utara, Medan. This study used a non-factorial completely randomized design, namely the salinity stress (S) which consisted of 3 levels, each treatment was repeated 3 times, so that 9 treatment combinations were obtained: the concentration of gibberelin was 0 (no treatment), 50 ppm and 100 ppm.